How can we improve self-isolation and quarantine for covid-19?. (10th March 2021) - Patel, Jay; Fernandes, Genevie; Sridhar, Devi
Abstract : Jay Patel and colleagues examine international approaches and argue for comprehensive support initiatives driven by local government and community based teams